Effect of organic dye on the growth and optical properties of KDP - Pritula, I.M.; Velikhov, Yu.N.; Levchenko, A.N.; Kolybayeva, M.I.; Puzikov, V.M.; Tyutyunnik, V.B.; Doroshenko, A.O. (Functional Materials, 2004)
It is established that Xylenol Orange (XO) preferentially dyes the faces {100} and {010} of KDP crystal. The dye content in the crystals is found to be practically independent of its content in the solution. It is revealed that the crystal habit changes in the presence of organic dyes: the ratio of the faces {100} and {010} (x and y) at maximum concentrations reaches 1.2. Studied is the influence of the mother solution acidity on the character of the crystal coloration. It is established that the color and dyeing intensity depend on the solution’s pH. The optical transmission spectrum of KDP with dye (solutions and crystals) is registered. The characteristic absorption peaks are observed in the region from 200 to 600 nm. Revealed is the transmission anisotropy in the directions x and y for the dyed crystals. Dichroism in KDP + XO is shown to depend on the orientation. The emission and excitation spectra of the dyed crystals are measured. The values of bulk laser damage threshold are determined. Discussed is the mechanism of the organic dye incorporation into the crystal matrix. Выращены кристаллы KDP с добавками органического красителя Xylenol Orange (XO). Показано, что XO преимущественно окрашивает грани {100} и {010} кристалла; (^одержание красителя в кристалле практически не зависит от его концентрации в растворе. Обнаружено изменение габитусa выращенных в присутствии органики кристаллов: отношение размеров граней {100} и {010} (х и у) при максимальных концентрациях красителя достигает 1,2. Изучено влияние кислотности маточного раствора на характер окрашивания кристалла. Установлено, что в зависимости от pH раствора изменяются как цвет, так и интенсивность окрашивания. Измерены спектры пропускания растворов и кристаллов KDP + XO в диапазоне длин волн 200-600 нм. Обнаружена анизотропия пропускания в направлениях х и у для окрашенных кристаллов. Показано, что дихроизм в KDP + XO является ориентационно зависимым. Измерены спектры возбуждения и люминесценции окрашенных кристаллов. Определены величины порога объемного лазерного разрушения. Обсуждается механизм вхождения органического красителя в кристаллическую матрицу. Вирощено кристали KDP з домішками органічного барвника Xylenol Orange (XO). Показано, що XO переважно забарвлює грані {100} і {010} кристала; вміст барвника в кристалі практично не залежить від його концентрації у розчині. Виявлено зміну габітусу кристалів, що вирощені у присутності барвника: відношення розмірів граней {100} і {010} (x і у) при максимальних концентраціях XO досягає 1,2. Вивчено вплив кислотності розчину на характер забарвлення кристала. Установлено, що в залежності від pH розчину змінюються як колір, так і інтенсивність забарвлення. Виміряно спектри пропускання розчинів і кристалів KDP + XO у діапазоні довжин хвиль 200-600 нм. Виявлено анізотропію пропускання у напрямках x і у для забарвлених кристалів. Показано, що дихроїзм у KDP + XO є орієнтаційно залежним. Виміряно спектри збудження та люмінесценції забарвлених кристалів. Визначено величину порога об’ємного лазерного руйнування. Обговорюється механізм входження органічного барвника у кристалічну матрицю .